The Extent of Awareness of Credit Decisions' Makers in Libyan Commercial Banks about the Role of Financial Indicators Derived from the Cash Flow Statement. - الجهني, أ.شعبان محمد (Dirasat in Economics and Business, 2021)
The aim of the research is to identify the extent of awareness of credit decisions' makers in Libyan commercial banks about the role of financial indicators derived from the cash flow statement. To achieve the goal of the research, one main hypothesis was formulated with three sub-hypotheses, which was testes on three commercial banks. Also, a modern scientific approach has been used, which is based on both inductive and deductive methods approach. The research found that decisions' makers in Libyan commercial banks were not aware of the role of financial indicators derived from the cash flow statement. Based on the findings, the research recommended that: The necessity of increasing the ability of credit officers to analyze accounting information and for companies to increase the degree of disclosure of accounting information published in the sta- tement of cash flows. In addition, pay attention to financial indicators derived from the cash flow statement when granting bank credit, and the need to direct their attention towards the importance of those indicators and their implications for the credit decision.